Influence of the surface coating on the cytotoxicity, genotoxicity and uptake of gold nanoparticles in human HepG2 cells. Issue 10 (25th March 2013) - Fraga, Sónia; Faria, Helena; Soares, Maria Elisa; Duarte, José Alberto; Soares, Leonor; Pereira, Eulália; Costa‐Pereira, Cristiana; Teixeira, João Paulo; de Lourdes Bastos, Maria; Carmo, Helena
ABSTRACT: The toxicological profile of gold nanoparticles (AuNPs) remains controversial. Significant efforts to develop surface coatings to improve biocompatibility have been carried out. In vivo biodistribution studies have shown that the liver is a target for AuNPs accumulation. Therefore, we investigated the effects induced by ~20 nm spherical AuNPs (0–200 μM Au) with two surface coatings, citrate (Cit) compared with 11‐mercaptoundecanoic acid (11‐MUA), in human liver HepG2 cells. Cytotoxicity was evaluated using the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) reduction and lactate dehydrogenase (LDH) release assays after 24 to 72 h of incubation. DNA damage was assessed by the comet assay, 24 h after incubation with the capped AuNPs. Uptake and subcellular distribution of the tested AuNPs was evaluated by quantifying the gold intracellular content by graphite furnace atomic absorption spectrometry (GFAAS) and transmission electron microscopy (TEM), respectively. The obtained results indicate that both differently coated AuNPs did not induce significant cytotoxicity. An inverse concentration‐dependent increase in comet tail intensity and tail moment was observed in Cit‐AuNPs‐ but not in MUA‐AuNPs‐exposed cells. Both AuNPs were internalized in a concentration‐dependent manner. However, no differences were found in the extent of the internalization between the two types of NPs. Electron‐dense deposits of agglomerates of Cit‐ and MUA‐AuNPs were observed either inside endosomes or in the intercellular spaces. In spite of the absence of cytotoxicity, DNA damage was observed after exposure to the lower concentrations of Cit‐ but not to MUA‐AuNPs. Thus, our data supports the importance of the surface properties to increase the biocompatibility and safety of AuNPs. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This study comparatively evaluated the influence of surface coating [citrate(Cit) vs 11‐mercaptoundecanoic acid(11‐MUA)] on the uptake and toxicity of gold nanoparticles(AuNPs) in HepG2 cells. Both Cit‐ and MUA‐AuNPs were observed either inside intracellular endosomes or in intercellular spaces. Under the tested conditions, they did not induce cytotoxicity. However, an inverse concentration‐dependent increase of DNA damage was observed in Cit‐AuNPs‐ but not in MUA‐AuNPs‐exposed cells. These data demonstrate the impact of surface properties in the biocompatibility and safety of AuNPs.